Modelling of surface morphology and roughness in fluid jet polishing. (15th March 2023) - Zhang, Zili; Cheung, Chi Fai; Wang, Chunjin; Guo, Jiang
Highlights: A physical prediction model of surface morphology and surface roughness for fluid jet polishing (FJP) was established. Computational fluid dynamics (CFD) simulation and kinetic analysis of the abrasives were conducted. The model considered the effect of jet pressure, abrasive sizes, and jet impinging angles on the material removal at multi-scale. The model was successfully validated by a series of polishing experiments. The influence mechanisms of polishing parameters on the surface roughness were revealed. Abstract: Fluid jet polishing (FJP) has been extensively used in various kinds of fields such as precision molding, optical components, etc. However, previous works mainly focused on the material removal process on the macro-scale (e.g., tool influence function, surface generation) to improve the form accuracy, the understanding of surface morphology evolution of FJP on the micro-scale is still far from complete, which makes it difficult to predict the surface quality under certain polishing conditions. Time-consuming and high-cost trial and error are usually needed to obtain suitable polishing conditions for specific surface quality requirements. In this paper, a physical model was developed to predict the surface morphology and roughness after FJP, by combining the computational fluid dynamics (CFD) simulation and kinetic analysis of the abrasives. The single abrasive erosion process including indentation action, ploughing action, and cutting action was analyzed by kinetic analysis. Besides, the overlap of single abrasive erosion pits was modeled to simulate the surface morphology evolution in FJP and determine the surface roughness after polishing. Different parameters were considered in the model including jet pressure, jet angle, and abrasive size. A series of polishing experiments were conducted to validate this model and the effect of different polishing parameters on surface quality was elucidated by the impact velocity distribution and erosion morphologies. It is found that the simulation results agree well with the experimental results. This paper not only provides a deeper understanding of the microscale material removal in FJP, but also provides an effective method for the prediction of surface roughness in FJP. Graphical abstract: Image, graphical abstract